2014
DOI: 10.1002/cctc.201402573
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Cinnamaldehyde to Cinnamal Alcohol over Platinum/Graphene Catalysts

Abstract: IntroductionThe selective hydrogenation of a,b-unsaturated carbonyl compounds is of theoretical and practical significance. [1][2][3] For instance, the hydrogenation of cinnamaldehyde (CAL) can produce cinnamal alcohol (COL), hydrocinnamaldehyde (HALD), and/or hydrocinnamal alcohol (HALC; Scheme 1), but the selective production of COL is difficult because the hydrogenation of the C=C bond is thermodynamically favored over that of the C=O moiety. [1,4] Moreover, acetals and other unidentified high-molecular-wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 57 publications
5
66
1
Order By: Relevance
“…23 Guo et al have shown that confinement of Pt nanoclusters within the cavity of metal-organic frameworks also promotes CinnOH selectivity; with steric constraints on CinnALD believed to hinder C=C planar adsorption with consequent preferential C=O activation. 24 Kinetics of CinnALD hydrogenation are also a function of support properties 25 and hydrogenation pressure. We recently reported a detailed mechanistic study of the structural and electronic factors controlling the liquid phase hydrogenation of cinnamaldehyde and related benzylic aldehydes over fumed SiO2 and mesoporous SBA-15 supported Pt nanoparticles.…”
mentioning
confidence: 99%
“…23 Guo et al have shown that confinement of Pt nanoclusters within the cavity of metal-organic frameworks also promotes CinnOH selectivity; with steric constraints on CinnALD believed to hinder C=C planar adsorption with consequent preferential C=O activation. 24 Kinetics of CinnALD hydrogenation are also a function of support properties 25 and hydrogenation pressure. We recently reported a detailed mechanistic study of the structural and electronic factors controlling the liquid phase hydrogenation of cinnamaldehyde and related benzylic aldehydes over fumed SiO2 and mesoporous SBA-15 supported Pt nanoparticles.…”
mentioning
confidence: 99%
“…In this work, the enhanced selectivity to COL caused by promoter Cu could be attributed to the increased fraction of the metallic Pt 0 species on the surface of the Pt-Cu/SiO 2 catalyst. According to our previous studies, the amount of Pt 0 on the catalyst has a much larger influence on the selectivity of COL, while the Pt 2+ and Pt 4+ species are responsible for the high-molecular-weight secondary products [13,[20][21][22]. For Pt/SiO 2 , there are more Pt 2+ and Pt 4+ species and less Pt 0 species, so it exhibits less selectivity to COL and higher selectivity to those condensation products.…”
Section: Catalytic Performancementioning
confidence: 91%
“…The unique advantage of such catalysts is that activity and selectivity can be tuned by controlling the size, shape, and surface species of Pt particles [1,[13][14][15]. In fact, many methods have been developed to enhance the performance of Pt-based catalyst, such as investigating novel support and promoter [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also have investigated in detail the CAL hydrogenation by using all sorts of catalysts consisting of Pt/Graphene [6], Pt/CNS and Pd/CNS [7], Pt-Mo 2 N/SBA-15 [8], Pd-WN/SBA-15 [9], and Co-Pt/SBA-15 [10]. In general, Pt [11][12][13], Ru [14,15], Au [16], Ir [17,18], Co [19,20], Cu [21,22] are conductive to the C=O bond hydrogenation to generate cinnamal alcohol (COL), while Pd [23,24], Rh [25,26], Ni [27][28][29] prefer a higher selectivity to the C=C bond, thus leading to the production of HALD.…”
Section: Introductionmentioning
confidence: 99%